Language Policy in Communication Between Students at UPN “Veteran” East Java Campus - Aufa Hanif Zakiyah; Firyal Syahirah; Shabrina Fadilah Ghaisani; Revina Ramadhani Putri Sembada; Teuku M. Amri Yahya Kusnan (Yayasan Sagita Akademia Maju, 2026)
Politeness in communication is an important aspect that affects social interaction among students, especially on campus. This study aims to analyse the form and level of politeness in communication among students at the National Development University